Longitudinal Immune Profiling of a Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection in a Solid Organ Transplant Recipient. (29th October 2021) - Klein, Jonathan; Brito, Anderson F; Trubin, Paul; Lu, Peiwen; Wong, Patrick; Alpert, Tara; Peña-Hernández, Mario A; Haynes, Winston; Kamath, Kathy; Liu, Feimei; Vogels, Chantal B F; Fauver, Joseph R; et al.
Abstract: Background: The underlying immunologic deficiencies enabling severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reinfection are currently unknown. We describe deep longitudinal immune profiling of a transplant recipient hospitalized twice for coronavirus disease 2019 (COVID-19). Methods: A 66-year-old male renal transplant recipient was hospitalized with COVID-19 March 2020 then readmitted to the hospital with COVID-19 233 days after initial diagnosis. Virologic and immunologic investigations were performed on samples from the primary and secondary infections. Results: Whole viral genome sequencing and phylogenetic analysis revealed that viruses causing both infections were caused by distinct genetic lineages without evidence of immune escape mutations. Longitudinal comparison of cellular and humoral responses during primary SARS-CoV-2 infection revealed that this patient responded to the primary infection with low neutralization titer anti–SARS-CoV-2 antibodies that were likely present at the time of reinfection. Conclusions: The development of neutralizing antibodies and humoral memory responses in this patient failed to confer protection against reinfection, suggesting that they were below a neutralizing titer threshold or that additional factors may be required for efficient prevention of SARS-CoV-2 reinfection. Development of poorly neutralizing antibodies may have been due to profound and relatively specific reduction in naive CD4 T-cell pools. Seropositivity alone may not be a perfect correlate of protection in immunocompromised patients. Abstract : Longitudinal profiling of immune responses for a renal transplant recipient who developed genotypically confirmed SARS-CoV-2 reinfection revealed poor-quality humoral immune responses, low neutralizing antibody presence, and depleted naive T-cell pools insufficient to protect against reinfection and no evidence of viral evasion.